2017
DOI: 10.1038/nphoton.2017.125
|View full text |Cite
|
Sign up to set email alerts
|

Valley-addressable polaritons in atomically thin semiconductors

Abstract: The locking of the electron spin to the valley degree of freedom in transition metal dichalcogenide (TMD) monolayers has seen them emerge as a promising platform in valleytronics [1,2]. When embedded in optical microcavities the large oscillator strengths of excitonic transitions in TMDs allow the formation of polaritons which are part-light part-matter quasiparticles [3][4][5][6][7]. Here, we report that polaritons in MoSe2 show an efficient retention of the valley pseudospin contrasting them with excitons an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
196
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(206 citation statements)
references
References 49 publications
8
196
1
1
Order By: Relevance
“…The well-defined optical transitions and negligible defect emission will allow us in the future to further explore these stable MoS 2 samples; for example, the exciton resonance can be tuned in resonance with optical cavity modes to explore strong coupling between light and matter in microcavities [7,8] with the added possibility of valley-specific optical excitations [88,89]. Also, all timeresolved experiments using pulsed laser, such as pumpprobe spectroscopy, time-resolved PL, and four-wave mixing [12,31,36,90,91], will benefit from these samples with much higher threshold for optical damage as compared to uncapped samples.…”
Section: Discussionmentioning
confidence: 99%
“…The well-defined optical transitions and negligible defect emission will allow us in the future to further explore these stable MoS 2 samples; for example, the exciton resonance can be tuned in resonance with optical cavity modes to explore strong coupling between light and matter in microcavities [7,8] with the added possibility of valley-specific optical excitations [88,89]. Also, all timeresolved experiments using pulsed laser, such as pumpprobe spectroscopy, time-resolved PL, and four-wave mixing [12,31,36,90,91], will benefit from these samples with much higher threshold for optical damage as compared to uncapped samples.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, upon the formation of exciton‐polaritons in open‐access microcavities, the expected valley depolarization by MSS mechanism is reduced, due to a decrease of random exciton momentum scattering by the fact that the spatial extension of polariton wavefunction is much larger than the length scale of the exciton disorder. The authors observed polarization retention of exciton‐polaritons with circular polarization degree up to 20%, compared to 2% and 5% for bare neutral and charged excitons . Furthermore, the authors reported valley coherent exciton‐polaritons in WSe 2 embedded in an open‐access microcavity in 2018 .…”
Section: Exciton‐polaritons In Open‐access Microcavitiesmentioning
confidence: 96%
“…The use of open‐access microcavities allows to explore and modify the intrinsic electronic properties of the monolayer material, best exemplified by the demonstration of valley addressable polaritons in MoSe 2 monolayers by Dufferwiel et al. in 2017 . It had been demonstrated in earlier literature that upon nonresonant excitation with circularly polarized light, the bare excitons in MoSe 2 monolayers almost does not retain the polarization of the pumped valley state, due to the Maialle–Silva–Sham (MSS) mechanism that a combined effect of the parallel and perpendicular (LT) spin splitting of exciton states and the random exciton momentum scattering results in a valley pseudospin relaxation.…”
Section: Exciton‐polaritons In Open‐access Microcavitiesmentioning
confidence: 99%
“…In addition to F‐P cavities formed by DBR mirrors, several other types of F‐P cavities were reported in the studies of EPs in TMDs. For example, TMD planar waveguides could serve as F‐P microcavities due to their capability of confining photons within the waveguide .…”
Section: Far‐field Spectroscopy Studies Of Eps In Tmdsmentioning
confidence: 99%